Turkey Red - Wertz, Julie (London : Bloomsbury Publishing, 2024)
"This multi-disciplinary study examines the exceptional Turkey red textile dyeing process and product. Prized for its brilliant colour and durability, yet notoriously difficult to produce, the textile was consumed locally and exported around the world. Considered one of the first instances of industrial espionage, the expansion of the Turkey red industry is closely linked to the Industrial Revolution and the emergence of a new global economy. Significant technological advances in chemistry and dyeing were motivated by the demands of Turkey red dyers and printers, who were located primarily in the west of Scotland, the north of England, and around Mulhouse, Switzerland. This book explores the arc of the Turkey red industry, the evolution of the process through key producers and technical developments, the complicated printing process, and finishes with an examination of significant Turkey red collections and a selection of object case studies. The chemistry of the process is described in an accessible, contextual manner, highlighting the significance of the distinctive technique that yielded the best red attainable on cotton. Drawing on both historical and contemporary study, Turkey Red presents significant new research on the material characterisation of this fascinating, eye-catching textile, and offers an in-depth historical example of the global effect of textile consumption."-- page 4 of cover
The Dyeing, Chemistry, and Technological Advances of Turkey Red 3.1 Oiling 3.1.1Oiling in the old process 3.1.2The chemistry of oiled cotton 3.1.3Ruminant dung and tannins 3.1.4Turkey red oil and the new process 3.1.5The Steiner process 3.2 Aluminium 3.2.1Precipitated aluminium soaps 3.3 Dyeing 3.3.1Color complexes in Turkey red 3.3.2 Blood and albumen 3.4. Clearing 3.5. Conclusions 4. Printed Turkey Red 4.1. Textile printing methods 4.2. Discharge printing 1.1.3.Lead plate press discharging 1.1.4.Acid paste discharging 4.3. A bright palette 1.1.5.Black, blue, yellow, and green 1.1.6.Identifying colorants on Turkey red prints 4.4. Design 1.1.7.Industrial design and production 1.1.8.European design for the export market 4.5. Conclusions 5. Turkey Red in the Industrial Revolution 5.1. Turkey red industry by country 5.1.1.France 5.1.2. England 5.1.3. Scotland 5.1.4. Switzerland 5.1.5. The Netherlands 5.1.6. North America 5.1.7. Other locations 5.2. Working conditions and labor 5.3.^
Gloss.
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Color in the textile industries -- History; Dyes and dyeing; Red; Textile industry -- Economic aspects; Textile industry -- Social aspects